Statistical modeling of the equine third metacarpal bone incorporating morphology and bone mineral density. - Helen Liley (PLoS ONE, 2018)
The objective of this study was to describe the three-dimensional shape and subchondral bone mineral density (BMD) variation of the equine distal third metacarpal bone (MC3) using a statistical shape model. The association between form and function builds upon previous two-dimensional observations of MC3 epiphyseal structure. It was expected that the main source of variation would be an increase in overall MC3 bone size, correlated to an increase in subchondral BMD. Geometry and bone mineral density was obtained from CT image data of 40 healthy Thoroughbred horses. This was used to create a statistical shape model, in which the first ten components described 75% of the variation in geometry and BMD. The first principal component described an increase in overall size of the MC3 distal epiphysis, coupled with higher BMD on the disto-palmar and dorso-proximal surfaces. The second component was qualitatively described as an increased convexity of the sagittal ridge at the dorsal junction of the epiphysis and the metaphysis, coupled to increased BMD in that region. The third component showed an increase in lateral condylar surface area relative to medial condylar area. As the condyle reduced in relative surface area, the BMD at both dorsal condyles increased. The statistical shape analysis produced a compact description of 3-D shape and sub-chondral bone mineral density variation for the third metacarpal bone. This study uniquely illustrates the shape variations in a sample population of MC3 bones, and the corresponding changes in subchondral BMD.